ISRO in Images - B N Suresh; P V Manoranjan Rao; V P Balagangadharan (Hyderabad, 2019)
This book celebrates the double anniversary through over 370 photographs, lovingly curated by the authors from a collection of 2000. Some of them have never been seen before by the public, while others are eye-catchingly beautiful.
English
Keywords: Astronautics; Engineering; ISRO